Airflow Pattern Simulation in Open Type Wind Tunnel with Test Section 40 cm X 40 cm X 80 cm: Simulasi Pola Aliran Udara pada Wind Tunnel Type Terbuka dengan Test Section 40 cm X 40 cm X 80 cm - Fakhruhrozi, Achmad Jakfar; Mulyadi, Mulyadi (Indonesian Journal of Innovation Studies, 2021)
This study aims to determine the pattern of wind flow in the open type wind tunnel and compare actual measurements and simulation results with software. The actual method used is testing using a wind tunnel, anemometer, dimmer, axial suction fan with parameters RPM 615, 1932, 2400,2860, and the simulation used using solidwork flow simulation software with parameters Inlet Velocity 1.4 m/s, 2.6 m /s, 3.9 m/s, 4.2 m/s. From the results of the study, it was found that the velocity of the air flowing through the wind tunnel channel obtained the largest value of 14.05 m/s and the smallest value of 0.5 m/s. has a different speed in each section which is influenced by the shape and dimensions of each section. in each section if the velocity is low the flow pattern is laminar, if the velocity is medium the flow pattern is transitional and if the velocity is high the flow pattern is turbulent. And the results of the comparison of actual and simulated velocity occur in the form of a similar flow pattern